(untitled) (Pedagogy of Higher and Secondary Education, 2011)
In the article influence of compatibility intellect and emotions of teacher of considered on the productivity of educational processin educational estabilishment. The retrospective review of illumination of the problem is done in artistic . The role of the external independent testing is considered as to one of forms of determination of IQ for students.